World Food Program - Climate Risk Profiles - Achicanoy Estrella, Harold Armando; Esquivel Arias, Alejandra; Ghosh, Aniruddha; Saavedra Vanegas, César Andrés; Ramírez Villegas, Julián Armando (2021)
Understand current and future climate hazards for: Burundi, Haiti, Guinea-Bissau, Guinee, Nepal, Niger, Pakistan, Somalia, and Tanzania